Expansion of higher education institutions and the intraurban spatial dynamics in Montes Claros/MG - SOUZA, CHRISTIAN YAGO VIEIRA DE; PEREIRA, ANETE MARILIA (Geografares, 2021)
The urbanization process in Montes Claros, as well as in many medium-sized Brazilian cities, occurred intensely in a short time. The industrialization, encouraged by the state in the 1970s, was one of the factors responsible for urbanization in Montes Claros. After several years, industry no longer represents the predominant activity in the municipal economy. The tertiary sector emerged as the most important and Montes Claros is currently the main reference in this sector in the North of Minas Gerais. Commercial activities and the provision of services, especially in the area of health and education, have changed the intra-urban dynamics and the city’s relations with its area of influence. In light of the foregoing, this article aimed to analyze the urban spatial dynamics arising from the expansion of Higher Education in Montes Claros. The methodological approach consisted of bibliographic research, secondary data collection, field work and interviews with representatives of Higher Education Institutions - HEIs, real estate agencies, commercial and service enterprises around the institutions, systematization of information and the preparation of maps. As a result, it was found that the expansion of the Higher Education service in Montes Claros led to the attraction of people from different locations, promoting demands for housing, goods and services, especially in the vicinity of the HEIs, streamlining specific areas of the city. It is also evident that the HEIs tend to be concentrated in specific areas of the city, generating diverse demands and changes in the surrounding space.